SISTEM INFORMASI PENDATAAN KELUARGA MISKIN DENGAN PARAMETER PENGHASILAN DAN KONDISI RUMAH DI DESA HUTARAJA - Adela Bintang Asari; Jamaluddin Jamaluddin; Rena Nainggolan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2021)
An information system is one of the systems that are currently a very appropriate tool. This information system is expected to help everything dealing with the population such as data collection on poor family residents. The current condition in the Hutaraja village head's office is that the data collection system for poor families is still running manually. Where in the application of this data collection system there are several things that become obstacles. The obstacles that occur are in terms of effectiveness, time efficiency, and accuracy of the data collection process. The current form of data collection report is still manual in nature which can complicate the process of finding data, and the possibility of data loss results from the data collection. With the above reasons, the writer tries to provide alternative solutions to the problem by making an application of data collection on poor families that will be made systematically and computerized. This writing will also explain the stages of work, starting from the process of analysis, planning, design using the PHP programming language (Hypertext Preprocessor), Boostrap Framework, and MYSQL database, with the aim to find out what data is input and output on the running system. With the existence of an information system on the collection of poor families, it is expected to be able to minimize the constraints that occur in the previous system and assist in the completion of the data collection of poor citizens and properly stored reports.